Social networking sites users' affective commitment: A combined view - Nan Zhang; Chong Wang; Yan Xu (International Telecommunications Society (ITS), 2012)
Social networking site has become ubiquitous in just a few years. Their success depends on users' intention to adopt and willingness to continue investing their time and attention in this media in the absence of formal contract. This study investigates the formation of people's affective commitment toward their online communities. Drawing on commitment theory and social network theory, I argue that the users' social network structure, specifically, online offline network overlapping, can influence the formation of their affective commitment toward the online community. Researchers seeking to understand users' behaviors on social networking sites can benefit from this study by considering the effect of network structure in their studies. Sites managers may also use our results to develop better functions for their users.
Keywords: 330; social networking site; social media; affective commitment; network overlapping